ORBITAL RADIOGRAPHIC ANATOMY. PART 2. ORBITAL SOFT TISSUE CONTENTS - O. Yu. Yatsenko; I. E. Tyurin (Вестник рентгенологии и радиологии, 2016)
Objective: to study the characteristics of orbital soft tissues in health. Material and methods. Computed tomography scans of 210 individuals (266 orbits) with no orbital abnormality were examined. Results. The paper presents the volumetric characteristics and parameters of the soft tissue density of the orbit and its apex (extraocular muscles, retrobulbar fat, optic nerve, lacrimal gland, eye, and vitreous body) in health. The internal surgical space fat at the orbital apex is estimated to be 75.35 and 73.83% of the total volume at the apex in men and women, respectively. The paper shows that individual asymmetry of orbital fat volumes in health is encountered in 47.61% of the men and in 51.42% of the women and ranges from 0.5 to 2.0 cm3. Conclusion. The volumes of orbital soft tissues in health are statistically significant different in the men and in the women. The asymmetry of the mean orbital soft tissue volumes in health is within the limits of statistical error.